Sertoli cell tumour in a neonate calf: an unusual congenital tumour - Vissiennon, Théophile; Freick, Markus; Kilic, Ergin; Schmidt, Thomas; Dänicke, Sven; Schmicke, Marion; Schneider, Eckard (Tierärztliche Praxis Ausgabe G: Großtiere / Nutztiere, 2016)
Congenital testicular tumours are seldom reported in bovine species. This case report describes the clinical, sonographical, haematological, pathomorphological and immunohistological features of a Sertoli cell tumour in a neonatal German Holstein calf. Microscopically, the enlarged testicle was composed of neoplastic cells, which were packed in well-formed tubules. The mostly polygonal shaped cells had round to elongated nuclei and a scanty eosinophilic cytoplasm. Some cells were arranged perpendicularly to the light PAS-positive basement membrane. These cells were packed in broad sheets separated by dense fibrous stroma. Mitotic figures were present. The features described above are indicative of a Sertoli cell tumour. The contralateral testicle showed a well formed rete testis, fusiform cells and a dense central capillary convolute and haemorrhagic foci. The features are indicative of an extensive fibrosis and older haemorrhage. The neoplasia was immunopositive for vimentin, α-oestrogen receptor, α-inhibin and S-100 protein, but immunonegative for cytokeratine, CD30, progesterone receptor, α-fetoprotein, SALL4, OCT4 and glypican-3. The myco - toxicological investigations revealed the presence of residues of zea - ra lenone, deoxynivalenol, ochratoxin, HT2 toxin and their metabolites in feeds and urine of heavily pregnant cows of the herd. Furthermore, information is provided about oestrogen and testosterone levels of the affected and healthy neonatal calves. A possible influence of mycotoxins on the cancerogenesis is discussed.
Keywords: Neonate; Sertoli cell tumour; immunophenotype; zearalenone; deoxynivalenol